Agricultural Science and Technology Indicators (ASTI) - International Food Policy Research Institute (International Food Policy Research Institute, 2000)
ASTI’s mission is to provide up-to-date quantitative and qualitative data and subsequent analyses on investment, capacity, and institutional trends in agricultural research and development (R&D) in low- and middle-income countries that will assist R&D managers and policymakers in improved policy formulation and decisionmaking at national, regional, and international levels. Informed policy decisions will have a positive impact on agricultural R&D systems and ultimately enhance productivity growth in agriculture, economic development, food security, and poverty reduction. The ASTI initiative has identified four objectives in fulfilling its mission: 1. provide up-to-date, high-quality datasets on agricultural R&D; 2. conduct further analysis of agricultural R&D datasets; 3. communicate data results and analysis for policy formulation and advocacy; and 4. build capacity for data collection and analysis Facilitated by the International Food Policy Research Institute (IFPRI), ASTI is a comprehensive and trusted source of information on agricultural R&D statistics. ASTI has published a broad set of country and regional reports and analytical publications that examine agricultural R&D trends at national, regional; and global levels, while at the same time providing comparative data on agricultural R&D performance across countries and regions. During its current phase (2012-14), ASTI is transforming itself from an ad-hoc data collection initiative to a sustainable and institutionalized system of data compilation, synthesis, and analysis at regular intervals through a set of national and regional focal points. Such a decentralized and institutional system will enhance ownership of the data and stimulate further advocacy and analysis at the national level. This transformation will initially focus on Sub-Saharan Africa and South Asia and will hopefully be rolled out to other regions in the near future.